THE JOINT SPATIAL PLANNING DATA MODEL - Yilmaz, Okan; Alkan, Mehmet (COPERNICUS GESELLSCHAFT MBH, 2023)
In modern times, spatial planning activities have been the process of determining projections for future land use. Spatial plans produce decisions about space in many different fields, from construction to transportation and environmental, natural, and cultural protection. The right, restrictions, and responsibilities (RRRs) to use the land pieces whose physical borders and legal status are registered with the cadastral process are determined by the spatial plans in line with the national purposes, public welfare, and healthy urbanization objectives. Land Administration Domain Model (LADM) is a general-purpose data model introduced in 2012 with International Organization for Standardization (ISO) standards. LADM proposes standards for many data infrastructures and land administration systems. In this context, although it does not have complete recommendations within the scope of spatial planning. It is essential to make additions to version II. As a result of gradual studies, spatial planning processes and decisions can be presented in a data model and the model can be associated with the LADM standard structure and integrated into land registration systems. Since LADM offers a conceptual model, newly created packages must be designed in a conceptual data model. The conceptual model is a product of several stages. This study focuses on how can produce a conceptual model in which countries can share spatial planning data. The requirements of the model that achieves this aim are revealed by considering the conceptual model production stages. By evaluating the findings, how can obtained data which helping to design the classes, class relations, and attributes of the data model were searched. With the conceptual data model to be prepared in line with the requirements, it is thought that land management processes can be strengthened by providing integration with spatial plans in LADM-based land administration systems.
Keywords: Spatial Planning; Land Administration; Data Modelling; LADM; Standardization; Georegulation; Computer Science; Remote Sensing